Activity‐dependent secretion of alpha‐synuclein by enteric neurons. (15th January 2013) - Paillusson, Sébastien; Clairembault, Thomas; Biraud, Mandy; Neunlist, Michel; Derkinderen, Pascal
Abstract There is growing evidence supporting a role of extracellular alpha‐synuclein in the spreading of Parkinson's disease (PD) pathology. Recent pathological studies have raised the possibility that the enteric nervous system (ENS) is one of the initial sites of alpha‐synuclein pathology in PD. We therefore undertook this survey to determine whether alpha‐synuclein can be secreted by enteric neurons. Alpha‐synuclein secretion was assessed by immunoblot analysis of the culture medium from primary culture of ENS. We show that alpha‐synuclein is physiologically secreted by enteric neurons via a conventional, endoplasmic reticulum/Golgi‐dependent exocytosis, in a neuronal activity‐regulated manner. Our study is the first to evidence that enteric neurons are capable of secreting alpha‐synuclein, thereby providing new insights into the role of the ENS in the pathophysiology of PD.